Gamificação no ensino de libras: explorando ferramentas digitais e estudos de caso para otimizar a aprendizagem de alunos surdos - Uchôa, Ana Kelly Rodrigues (Brasil, 2024)
The use of new technologies in teaching deaf subjects promotes inclusion and accessibility, allowing the use of resources such as sign language translators, specific educational applications and online platforms, expanding learning and communication opportunities for this community. In this context, gamification emerges as a tool that aims to facilitate the teaching process, both for the student and the teacher. Therefore, this research is dedicated to understanding the challenges, benefits and way in which this new way of teaching The use of digital games can add qualifications and facilities to the teaching process, placing emphasis on teaching deaf students.